Diesel soot coated non-woven fabric for oil-water separation and adsorption applications - Sharma, Moolchand (Sci Rep, 2019)
The diesel soot (DS) coated non-woven fabric was studied for oil-water separation along with the adsorption of dyes, detergents, and pharmaceuticals. The DS coated non-woven fabric showed more than 95% separation efficiency and consistent repeatable performance during oil-water separation experiment. In addition to this, the DS coated non-woven fabric of 17.2 cm(2) area successfully adsorbed ~85%, 97%, and 100% methylene blue (MB) dye, ciprofloxacin, and detergent, respectively from their respective solutions within 30 min, which was not possible using uncoated non-woven fabric. The DS coated non-woven fabric was found to be hydrophobic with the contact angle of 140° which was almost invariant upto 60 °C. Hence, the DS coated non-woven fabric showed promising performance in the oil-water separation and adsorption applications.